PP.42.08: STUDY OF THE ASSOCIATIONS BETWEEN COMMON VARIANTS IN THE LAMP2 GENE, BLOOD PRESSURE AND MYOCARDIAL INFARCTION IN A MEDITERRANEAN POPULATION. (June 2015) - Corella, D.; Coltell, O.; Godoy, D.; Sorlí, J.V.; Asensio, E.M.; Guillén, M.; González, J.I.; Macian, F.; Cuervo, A.M.
Abstract : Objective: Chaperone-mediated autophagy is a selective form of autophagy by which cytosolic proteins are recognized by a chaperone complex which targets them to lysosomes for degradation. The lysosomal uptake of these proteins requires their binding to the lysosome-associated membrane protein type 2A (LAMP-2A). LAMP-2A is one of the three splice variants of the LAMP2 gene, localized to Xq24. Mutations in LAMP2 are associated with development of hypertrophic cardiomyopathy and with other phenotypes related to Danon disease. However, the effects of common polymorphisms in the LAMP2 gene on blood pressure and cardiovascular diseases (CVD) are not known. Our objective was to investigate the association of common LAMP2 variants with blood pressure and myocardial infarction incidence in a high cardiovascular risk population. Design and method: We analyzed the participants in the PREDIMED-Valencia Study (n = 1094). PREDIMED is a multicenter randomized controlled trial aimed at assessing the effects of the Mediterranean diet in the prevention of CVD. Participants were high cardiovascular risk subjects, aged 67 ± 7 y. Blood pressure was measured at baseline by triplicate and clinical and lifestyle variables were obtained. Incidence of myocardial infarction (fatal and non-fatal) was identified after a median of 4.8 y follow-up. Common LAMP-2 polymorphisms (rs2748 and rs42889) were determined. Multivariable regression models were fitted to test associations. Results: Prevalence of the selected polymorphism (both intronic, in the 3UTR and in partial linkage disequilibrium) was as follows; in women: 40.9% TT, 41.1% TC and 18.0% CC for rs2748 and 37.8% CC, 44.4% CT and 17.8% TT for rs42889. In men: 46.2%T and 53.8% C (rs2748) and 57.2% C and 42.8% T (rs42889). We did not find any significant association between the polymorphisms and blood pressure (systolic or diastolic) at baseline. However we found a significant association of the rs42889 with myocardial infarction in women. Carriers of the variant allele had lower risk than CC homozygotes even after adjustment for age, dietary intervention, type-2 diabetes and smoking (OR: 0.19; 95% CI:0.04–0.94; P = 0.042). Conclusions: Our results suggest a potential role of the common LAMP2 polymorphism on myocardial infarction in women that requires further investigation.